Pengaruh Interaksi Mikroalga Chlorella Sp. Dan Bakteri Bioprisma Terhadap Penurunan Kadar Nitrogen Total Pada Medium Limbah Cair Tahu - Lely Rahmawati Saragih; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Tofu liquid waste can be utilized by microalgae Chlorella sp. as a source of nutrition for its growth.Utilization of nutrients by Chlorella sp. can reduce total nitrogen of tofu liquid waste. The purposes of this research is to know the interaction between a complex microorganism contained in Bioprisma as a decomposer agent with the addition of photosynthetic microalgae Chlorella sp. as an oxygen producer in reducing total nitrogen loads of tofu liquid waste. The study conducted in batches with the bacteria addition treatment in 5 different levels, that is 0 (without the addition of bacteria), addition of bacteria as many as 0,25; 0,50; 0,75 and 1 (% v/v). The processing is carried out for 13 days with solar irradiation in the photobioreactor. The treatment with the addition of 1% was able to reduce total Nitrogen with 71,89% removal efficiency at the best-removing detention time, happened in days-13.Keywords: Chlorella sp., Bioprisma, Tofu Liquid Waste,Total Nitrogen, Contact Time.